2015
DOI: 10.1016/j.ijsu.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

A review of the incidence of iatrogenic hernia in both laparoscopic and open colorectal surgery: Using CT as the gold standard of detection, cohort study

Abstract: The incidence of iatrogenic hernias is underestimated. The use of CT will increase the number detected. There is no significant difference in the incidence of iatrogenic hernias between laparoscopic and open colorectal procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
2
14
0
3
Order By: Relevance
“…Research has demonstrated the equivocal effects of laparoscopy on incisional hernias and adhesion-related SBO[ 35 36 37 ] Our findings are consistent with the long-term results of other studies. [ 37 38 ] Therefore, the results confirm that for radical resection of CRC, the safety of MIT is comparable to that of CL.…”
Section: Discussionsupporting
confidence: 65%
“…Research has demonstrated the equivocal effects of laparoscopy on incisional hernias and adhesion-related SBO[ 35 36 37 ] Our findings are consistent with the long-term results of other studies. [ 37 38 ] Therefore, the results confirm that for radical resection of CRC, the safety of MIT is comparable to that of CL.…”
Section: Discussionsupporting
confidence: 65%
“…The diagnosis of IH was based on a combination of radiology and physical examination. Previous studies have reported that 20%–30% of IH cases are missed when only physical examination, as opposed to CT, is performed . Ultrasonography may also be used, and it can increase the diagnostic yield by at least 20% .…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard of IH diagnosis is CT imaging with Valsalva maneuver, because a clinical examination can be problematized by obesity, abdominal pain, and previous surgery of the abdominal wall [ 26 , 27 ]. The CT images in the present study were obtained primarily to detect any sign of cancer recurrence and therefore performed without the Valsalva maneuver; thus, such a CT scan has a low sensitivity to detect IH.…”
Section: Discussionmentioning
confidence: 99%